PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PROFESIONALISME GURU DI MI MI’RAJUL ULUM TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANSING - Riska Rinda (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This study aims to determine the effect of the principal's leadership on teacher professionalism at MI Mi'rajul Ulum Teluk Beringin and to determine the factors that influence the leadership of school principals on teacher professionalism in MI Mi'rajul Ulum Teluk Beringin. Haisl's observations made at MI Mi'rajul Ulum Teluk Beringin showed several symptoms as follows: 1) There were teachers who taught not according to their expertise. 2) There are teachers who do not prepare and prepare learning tools. 3) The method used is menoton. 4). Students often fight at school. 5) Lack of collegiality among teachers. The data collection techniques used were observation, questionnaires, and documentation. In processing data using simple linear regression analysis techniques with the help of SPSS. Based on the percentage achieved in this study, it can be seen that the leadership of the school principal at MI Mi'rajul Ulum Teluk Beringin made a significant contribution. The regression equation is Y = 17.829 + 0.585X. From this equation, the principal leadership coefficient value is 0.585 which means, if the principal's leadership increases by one unit, the teacher professionalism will increase by 0.585 units. After knowing the influence between the two variables, it is continued by looking for the coefficient of determination, to find out how much the principal's leadership contributes to teacher professionalism. Thus, the magnitude of the influence of the principal's leadership on teacher professionalism at MI Mi'rajul Ulum Teluk Beringin is 58.5% which means it has influence while 41.5% is influenced by other factors. Keywords: principal leadership, teacher professionalism at MI Mi'rajul Ulum Teluk Beringin